THE EFFECT OF MAKING A MATCH TO INCREASE STUDENTS’ WRITING SKILL - Amrizal Amrizal; Zohri Hamdani (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
This study aimed to know the effect of making a match to increase students writing skill especially sentence pattern “noun + verb + adverbial. True experimental design was used in this study. The data of collecting technique used pretest and posttest, the population was 30 students English Education, the first semester, State of Islamic College (STAIN) Mandailing Natal, the sample used experimental group and control group. The analysis data used SPSS 16.0. The result of this study shows that students had better achievement in writing skill when learning writing used make a match method.